A Statistical Analysis of Effectiveness of Energy Policy in the United States: Incentives vs. Regulations. (2015) - Lee, Seungtaek; Kim, Yeowon; Chong, Wai K.
Abstract: The increase of greenhouse gas emissions in the atmosphere has affected the global climate. The federal, state and local governments are mostly concerned with the environment, so they have developed and/or implemented environmental policies to reduce greenhouse gas emissions in the United States. Increasing renewable energy use and improving energy efficiency are some of the strategies for reducing greenhouse gas emissions. Each state has its own set of regulations and incentive policies to address energy use and supply, and these are constantly updated to reflect changing conditions. Failed policies are often extracted, while successful policies continued (pending availability of funds). Thus, it is necessary to verify which kinds of policies are helpful to increase the usage of renewable energy and energy efficiency methods. The main objective of this research was to understand how influential different kinds of policies would be in encouraging renewable energy use and improving energy efficiency. Based on the analyses, the research team identified the key factors of a successful energy policy. This research systematically reviewed environmental policies and investigated their effectiveness. Most importantly, policymakers can utilize the factors that influence their energy policies.